2018
DOI: 10.18378/rvads.v13i3.5771
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade de cultivares de alface em função da idade de colheita no semiárido Potiguar, Brasil

Abstract: No Nordeste brasileiro, o cultivo da alface restringe-se a pequenas áreas, com a utilização de cultivares pouco adaptadas às condições climáticas da região, dessa forma, ocorre o florescimento precoce e baixa produtividade. Diante disso, a pesquisa foi realizada objetivando-se avaliar as respostas agronômicas de cultivares de alface em função da idade de colheita, quando cultivadas em condições semiáridas. O experimento foi conduzido em campo, entre os meses de outubro de 2013 e janeiro de 2014, em Mossoró, Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
1
5
0
2
Order By: Relevance
“…The number of leaves varied between 14.65 and 27.60 leaves per plant; Baba-de-Verão (Lisa) had larger number than the other Crespa cultivars, which did not significantly differ from each other (Table 2). These results are consistent with those found by Souza et al (2018), who evaluated lettuce cultivars with different ages at harvest during the springsummer in Mossoró, RN, Brazil (Semiarid region) and found 32.92, 31.60, and 32.17 leaves per plant for Lisa lettuce cultivars (Baba-de-Verão, Livia, and Aurelia), respectively, at 30 DAT, with larger numbers than the Crespa cultivars.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The number of leaves varied between 14.65 and 27.60 leaves per plant; Baba-de-Verão (Lisa) had larger number than the other Crespa cultivars, which did not significantly differ from each other (Table 2). These results are consistent with those found by Souza et al (2018), who evaluated lettuce cultivars with different ages at harvest during the springsummer in Mossoró, RN, Brazil (Semiarid region) and found 32.92, 31.60, and 32.17 leaves per plant for Lisa lettuce cultivars (Baba-de-Verão, Livia, and Aurelia), respectively, at 30 DAT, with larger numbers than the Crespa cultivars.…”
Section: Resultssupporting
confidence: 91%
“…Baba-de-Verão presented a similar fresh matter yield to those of the cultivars Elba (19.81 Mg ha -1 ), Mônica (20.04 Mg ha -1 ), Solaris (20.72 Mg ha -1 ), and Veneranda (19.34 Mg ha -1 ). Similarly, Souza et al (2018) found 28.08 Mg ha -1 for Babade-Verão when harvested at 35 DAT in Mossoró, which differed from the cultivars Livia (23.38 Mg ha -1 ), Aurelia (20.12 Mg ha -1 ), Jullie (23.22 Mg ha -1 ), Elba (23.16 Mg ha -1 ), and Maravilha 4 Estações (22.80 Mg ha -1 ). The higher yield of Baba-de-Verão may be connected to its adaptability to the high temperature of the region (SOUZA et al, 2018).…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Ela é originada da região do mediterrâneo, onde predomina o clima temperado, por isso é bastante sensível à luminosidade e temperatura elevada, faixas acima de 20°C promovem o aparecimento de distúrbios fisiológicos (SOUZA et al, 2018). Diante disso, é fundamental que se faça uma escolha adequada da cultivar de alface que será cultivada em função do clima.…”
Section: Introductionunclassified